The Effect of the Indoor Residual Spraying (IRS) Program on Reducing Parasite Incidence in the Working Area of the Sea Silau Health Center, Asahan District - Ice Ratnalela Siregar; Mardan Ginting; Theodorus Teddy Bambang (Journal of Social Research, 2023)
Malaria is a severe, life-threatening infectious disease transmitted through the bite of infected female Anopheles mosquitoes. In Asahan Regency, four areas are endemic for malaria, with Silau Laut District having an API rate of 4.8‰ (Annual Parasite Incidence per 1000 at-risk individuals annually). Indoor residual spraying (IRS) with Lambda Cyhalothrin (Icon 100 CS) is used to eradicate mosquito vectors by applying insecticide to walls and ceilings, interrupting transmission. Research aimed to assess IRS effectiveness in reducing malaria incidence in Silau Laut District found a strong positive correlation (0.826 and 0.912) between RDT and microscopic examination results before and after IRS. However, correlations between education and malaria control using IRS and changes in knowledge and attitudes were weak (0.490 and 0.438). Paired T-tests revealed differences in RDT examination results (p = 0.044) and knowledge and attitude levels (p = 0.000) before and after IRS education. No significant difference was observed in microscopic examination results (p = 0.159). Recommendations include intensified efforts in malaria prevention and control, including active case finding, mosquito nest elimination, continued IRS, mesh installation, insecticide-treated bed net use, health education, and regular bioassay testing every 1-2 months for 3-6 months in Silau Laut District.